Multimodal Label‐Free Monitoring of Adipogenic Stem Cell Differentiation Using Endogenous Optical Biomarkers. (6th August 2021) - Mehta, Nishir; Shaik, Shahensha; Prasad, Alisha; Chaichi, Ardalan; Sahu, Sushant P.; Liu, Qianglin; Hasan, Syed Mohammad Abid; Sheikh, Elnaz; Donnarumma, Fabrizio; Murray, Kermit K.; Fu, Xing; Devireddy, Ram; et al.
Abstract: Stem cell‐based therapies carry significant promise for treating human diseases. However, clinical translation of stem cell transplants for effective treatment requires precise non‐destructive evaluation of the purity of stem cells with high sensitivity (<0.001% of the number of cells). Here, a novel methodology using hyperspectral imaging (HSI) combined with spectral angle mapping‐based machine learning analysis is reported to distinguish differentiating human adipose‐derived stem cells (hASCs) from control stem cells. The spectral signature of adipogenesis generated by the HSI method enables identifying differentiated cells at single‐cell resolution. The label‐free HSI method is compared with the standard techniques such as Oil Red O staining, fluorescence microscopy, and qPCR that are routinely used to evaluate adipogenic differentiation of hASCs. HSI is successfully used to assess the abundance of adipocytes derived from transplanted cells in a transgenic mice model. Further, Raman microscopy and multiphoton‐based metabolic imaging is performed to provide complementary information for the functional imaging of the hASCs. Finally, the HSI method is validated using matrix‐assisted laser desorption/ionization‐mass spectrometry imaging of the stem cells. The study presented here demonstrates that multimodal imaging methods enable label‐free identification of stem cell differentiation with high spatial and chemical resolution. Abstract : Multimodal methods using hyperspectral, Raman, and second harmonic generation imaging are demonstrated to identify differentiated and control adipogenic stem cells. The study is validated using mass spectrometry, and the endogenous optical markers are identified.